Environmental Education and curricular designs for Basic Secondary Education in the province of Buenos Aires: critical analysis in the context of the new national legislation: a study in Secondary schools in the Province of Buenos Aires (Praxis Educativa, 2023)
The forms in which Environmental Education (EE) is included in the curriculum are a long-standing concern in the Latin American didactic field. In this paper we analyse the current curricular designs for the Basic Secondary School in the province of Buenos Aires, Argentina. Although in hierarchically superior regulations (Provincial Education Law and General Framework of Curricular Policy), EE is based on critical and ethnographic perspectives, it has an uneven transversal presence in the curricular designs. Some subjects present an empty EE curriculum, while others show fragmentary and contradictory perspectives. Only in Social Sciences, Geography and Citizenship Building is there a critical and ethnographic vision, linked to contemporary environmental conflicts. From Geography we recovered the experiential dimension and the enjoyment of the environment as a contribution to the pedagogies of environmental conflict and to the ongoing implementation the new national EE regulations.
Keywords: environmental education; secondary education; school curriculum; curricular design; educational legislation